Factors of Local E-Government Development in Poland: The Case of the Poznań Agglomeration - Perdał, Robert (Quaestiones Geographicae, 2016)
This paper seeks to analyse factors of e-government development at the local government level in Poland. The analysis proceeded in three stages. In the first, a survey of the literature on the subject was made and a model of factors of e-government development was constructed. In the second, the factors distinguished were operationalised: indicators representing them were constructed. The third stage involved an empirical verification of the model using partial correlation and multiple regression methods; significant factors of e-government development were distinguished at the local government level. The analysis was conducted for a group of 18 communes making up the Poznań agglomeration. It was demonstrated that significant factors of local e-government development in Poland included the level of socio-economic development, inhabitants’ access to ICT, their attitudes and skills, the size of administrative units, attitudes of local authorities and leaders, a vision and a strategy of e-government development, human resources in offices, and the financial situation of a commune.